PENERAPAN SANKSI PIDANA DAN TINDAKAN TERHADAP ANAK MENURUT UU NO. 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Andhik Eko Susanto (MIZAN, Jurnal Ilmu Hukum, 2022)
Sanction fallout represent the power appliance to strengthen to to go into effect a norm and to prevent and also fight against the action bothering to go into effect a norm. Target which wish reached from sanction fallout to child to be the child can be mixed return to society. Double Track system represents the system two band concerning sanction in criminal law that is sanction of crime and type of action sanction. Even if in practice, difference between sanction of crime and action sanction often rather hazy, but elementary idea storey; level both owning elementary difference, whereabouts crime sanction coming from the elementary idea "why performed by crime". Target in this research is: (1) For the describe of applying of sanction of crime and action to child conducting doing an injustice. (2) For the describe of consideration punish the judge in knocking down sanction of crime and action to child conducting doing an injustice. Conclusion of result of this research is: (1) Applying of sanction of crime and action to child conducting doing an injustice at 2 justice decision namely Number 08/Pid.Sus Anak/2014/Pn.Mrs have pursuant to Section 71 article 1 letter e namely Fallout of Crime Sanction which is in the form of prison during 7 month; moon and Number Decision 114/Pid.Sus-Anak/2014/PN.Mrs have pursuant to Section 69 Article 2 and Section 82 article 1 letter a namely Action Fallout which is in the form of return to parent in Number Law 11 Year 2012 About System Of Judicature of Child Crime. (2) Consideration punish the judge in knocking down sanction of crime and action to child conducting doing an injustice at 2 decision of Number Justice 08/Pid.Sus/Anak/2014/PN.Mrs and Number Decision 114/Pid.Sus-Anak/2014/PN.Mrs is fulfilled of all section elements in assertion, and also boldness of eyewitness and defendant boldness which each other correspond added with the judge confidence. According to Judge Writer knock down the crime to child with an eye to crime to give the effect discourage the defendant and to be defendant do not repeat its deed again. Keyword: Crime sanction, action, system of judicature of child crime.